The enlightened Chinese characters : a cognitive approach of computer assisted Chinese character learning - Yang, Wan Chi (Ada Yang) (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MPhil (Modern Foreign Languages))--University of Stellenbosch, 2006.